THE INFLUENCE OF THE FIRST COOPERATIVE LAW ON ENHANCING OUTREACH ACTIVITIES OF COOPERATORS - Z. R. Kochkarova (Гуманитарные и юридические исследования)
The article studies the influence of the first cooperative law as regards the enhancement of outreach activities on the part of cooperators, on the self-consciousness of the masses in organizing cooperatives to improve their material and spiritual needs. The article features first-time analysis of the impact of the cooperative law to enhance and institutionalize cooperation. It is shown that cultural and educational department of the Council of the All-Russia congress of cooperative fostered cooperative activities.